Vertebral marrow fat fraction is associated with circulating RANKL in postmenopausal females - Li, Xuefeng; Zuo, Xiaoyong; Lu, Li; Xu, Run; Wang, Ying; Chang, Shixin; Wang, Yi; Luo, Peng; Li, Guanwu (Frontiers in Endocrinology, 2024)
Objective: To investigate the relationship between circulating receptor activator of nuclear factor-kappa B ligand (RANKL) levels and marrow adipose tissue in postmenopausal females. Methods: A total of 164 postmenopausal females were included in the study. Serum levels of osteoprotegerin (OPG) and RANKL were measured using ELISA kits. Body composition and bone mineral density (BMD) were assessed using dual-energy X-ray absorptiometry. Complex-based chemical shift imaging-based MRI was employed to evaluate the vertebral marrow proton density fat fraction (PDFF). A multivariate linear regression model was utilized to analyze the predictive effects of PDFF and BMD on circulating levels of OPG and RANKL. Results: Simple regression analysis showed significant associations among the marrow PDFF, BMD at either site, serum RANKL, and the RANKL/OPG ratio. In multivariate linear regression models, marrow PDFF was found to have a positive correlation (β = 3.15, 95% CI 2.60 to 3.70) and BMD had negative correlations (β = 0.200, 95% CI 0.348 to 0.051 for vertebral BMD; β = 0.383, 95% CI 0.589 to 0.177 for total hip BMD; and β =0.393, 95% CI 0.598 to 0.188 for femoral neck BMD, all p < 0.01) with circulating soluble RANKL levels after adjusting for age, body mass index, physical activity, total fat mass, android/gynoid ratio, and lean mass. Similar results were observed for the RANKL/OPG ratio. Additionally, multivariate linear regression analyses revealed that marrow PDFF was a significant independent contributor of circulating soluble RANKL (β = 1.34, 95% CI 1.10 to 1.58, p < 0.001) after further controlling for BMD. However, marrow PDFF or BMD had no associations with circulating levels of OPG after adjusting for all potential confounders mentioned above. Conclusions: Vertebral marrow fat fraction is independently associated with circulating soluble RANKL levels in postmenopausal females.